Reliability and Validity of the Korean Version of the Pain and Sleep Questionnaire and in Relation to Pain-Specific Sleep-Related Cognition - Sajida Fawaz Hammoudi; Seockhoon Chung (Sleep Medicine Research)
Background and Objective We investigated the reliability and validity of the Korean versions of the Pain and Sleep Questionnaire-5 (PSQ-5) and PSQ-3 among patients with chronic pain. Methods An anonymous online survey was conducted with chronic pain patients. Participants’ demographic information was collected, along with responses to rating scales including the PSQ-3 and PSQ-5, the Pain-related Beliefs and Attitudes about Sleep (PBAS) Scale, Dysfunctional Beliefs and Attitudes about Sleep-6 items (DBAS-6), Dysfunctional Beliefs about Sleep-2 items (DBS-2), the Insomnia Severity Index (ISI), pain severity measured using a numeric rating scale, and the discrepancy between desired time in bed and desired total sleep time (DBST index). Results Confirmatory factor analysis demonstrated good model fits for both PSQ-5 and PSQ-3. Both the PSQ-5 and PSQ-3 exhibited high reliability of internal consistency, with Cronbach’s alphas of 0.904 (PSQ-5) and 0.903 (PSQ-3), respectively. The PSQ-5 was significantly correlated with pain severity (r=0.58, p<0.001), PSQ-3 (r=0.96, p<0.001), PBAS (r=0.86, p<0.001), DBAS-6 (r=0.50, p<0.001), DBS-2 (r=0.42, p<0.001), and ISI (r=0.67, p<0.001). The PSQ-3 also demonstrated good convergent validity with these scales. Mediation analysis indicated that pain severity directly influenced both the PSQ-5 and PSQ-3 scores, with the PBAS mediating this association. Conclusion s The Korean versions of the PSQ-3 and PSQ-5 are validated and reliable tools for evaluating sleep quality in patients with chronic pain.